Determining Product Quality And Halal Labeling Through Positive Emotion On Lemonilo Purchase Intention - Yudha Trishananto; Ali Ikhsan (Journal of Islamic Enterpreneurship and Management, 2024)
This research analyzes "The Influence of Product Quality and Halal Labels on Intention to Repurchase Lemonilo Instant Noodle Products among UIN Salatiga Students, with Positive Emotion as an Intervening Variable." The sample used in this research was 100 respondents from UIN Salatiga students. So the instruments used in this research are validity test, reality test, classical assumption test, hypothesis test and path analysis test, based on the results of the analysis that has been carried out, variables include "The Influence of Product Quality and Halal Labels on Intention to Repurchase Noodle Products Instant Lemonilo on UIN Salatiga Students, with Positive Emotion as an Intervening Variable, can be concluded as follows. The effect of product quality on repurchase interest is not significant, the halal label has a positive and significant effect on repurchase interest, product quality has a negative and insignificant effect on positive emotion, the halal label has no positive and significant effect on positive emotion, repurchase interest has a positive effect and significant for positive emotion, positive emotion is able to mediate the influence of product quality on repurchase interest, positive emotion is able to mediate the influence of the halal label on repurchase interest.